FOSTERING STUDENTS’ DISCIPLINE THROUGH EXTRACURRICULAR ACTIVITIES AT MADRASAH IBTIDAIYAH - Siti Marjiyah; Abdul Wachid BS (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study was conducted to describe the improvement of students’ discipline through extracurricular activities at Madrasah Ibtidaiyah. The method of this research was descriptive qualitative. The data were collected through interviews and observations with descriptive data analysis. Then, the data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that extracurricular activities increased the students’ discipline at Madrasah Ibtidaiyah Muhammadiyah, Purbalingga. This activity was a school program which contained rules or regulations that must be implemented by students so that the students’ discipline increased. All extracurricular activities were performed at Madrasah Ibtidaiyah Muhammadiyah Purbalingga supervised by educators at the madrasah.